Biochemistry of Antioxidants: Mechanisms and Pharmaceutical Applications - Sonia Losada-Barreiro; Zerrin Sezgin-Bayindir; Fátima Paiva-Martins; Carlos Bravo-Díaz (Biomedicines, 2022)
Natural antioxidants from fruits and vegetables, meats, eggs and fish protect cells from the damage caused by free radicals. They are widely used to reduce food loss and waste, minimizing lipid oxidation, as well as for their effects on health through pharmaceutical preparations. In fact, the use of natural antioxidants is among the main efforts made to relieve the pressure on natural resources and to move towards more sustainable food and pharmaceutical systems. Alternative food waste management approaches include the valorization of by-products as a source of phenolic compounds for functional food formulations. In this review, we will deal with the chemistry of antioxidants, including their molecular structures and reaction mechanisms. The biochemical aspects will also be reviewed, including the effects of acidity and temperature on their partitioning in binary and multiphasic systems. The poor bioavailability of antioxidants remains a huge constraint for clinical applications, and we will briefly describe some delivery systems that provide for enhanced pharmacological action of antioxidants via drug targeting and increased bioavailability. The pharmacological activity of antioxidants can be improved by designing nanotechnology-based formulations, and recent nanoformulations include nanoparticles, polymeric micelles, liposomes/proliposomes, phytosomes and solid lipid nanoparticles, all showing promising outcomes in improving the efficiency and bioavailability of antioxidants. Finally, an overview of the pharmacological effects, therapeutic properties and future choice of antioxidants will be incorporated.